2019
DOI: 10.3390/app9091767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waste Engine Oil and Waste Cooking Oil on Performance Improvement of Aged Asphalt

Abstract: In order to explore the applicability of waste engine oil and waste cooking oil used in aged asphalt, the effect of waste engine oil and waste cooking oil on aged asphalt recycling was studied through the analysis of the improvement of its physical, chemical, and rheological properties. Six aged asphalt binders with different aging times were obtained by indoor test simulation using the Thin Film Oven Test at 163 °C. Then, waste engine oil and waste cooking oil with five different dosages were added to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 24 publications
0
28
0
2
Order By: Relevance
“…Moreover, the use of waste cooking oil is an eco-friendly solution due to its great performance as a rejuvenating agent [ 110 , 111 , 112 , 113 , 114 , 115 ]. Similarly, waste mineral oils can be reused as rejuvenators without further refinement [ 115 ], although vegetal oil-based rejuvenators usually require lower doses than the ones based on petroleum to achieve similar performance [ 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. Another green option to produce rejuvenators is the use of organic waste to obtain bio-oil [ 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of waste cooking oil is an eco-friendly solution due to its great performance as a rejuvenating agent [ 110 , 111 , 112 , 113 , 114 , 115 ]. Similarly, waste mineral oils can be reused as rejuvenators without further refinement [ 115 ], although vegetal oil-based rejuvenators usually require lower doses than the ones based on petroleum to achieve similar performance [ 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. Another green option to produce rejuvenators is the use of organic waste to obtain bio-oil [ 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Organic rejuvenators require lower dose than petroleum-based rejuvenators to yield similar effects on the rheological properties [37]. Upon comparing the efficacy between WCO and WEO, the former restored the original rheological properties more effectively than the latter [60].…”
Section: Rejuvenation Of Recycled Asphalt Using Refined Crude-oilsmentioning
confidence: 99%
“…The WEO-asphalt adhesion was enhanced with an anti-stripping agent, whilst the blend failed at high temperature. Next, Li et al [60] reported that WCO and WEO enhanced the properties (ductility, penetration, and softening point) of aged asphalt. Nonetheless, lower amount of WCO demonstrated a similar rejuvenation impact displayed by WEO; signifying WCO as the better rejuvenator than WEO.…”
Section: Rejuvenation Of Recycled Asphalt Using Refined Crude-oilsmentioning
confidence: 99%
“…Lahan yang tersedia semakin sempit sementara jumlah limbah yang dihasilkan terus meningkat seiring dengan pertambahan penduduk dan kemajuan teknologi. Dalam bidang transportasi, sudah terdapat banyak penelitian dan implementasi pemanfaatan limbah, terutama untuk struktur perkerasan, seperti limbah plastik plastik sebagai pengganti agregat, limbah minyak sebagai peremaja aspal, dan limbah metal sebagai perantara panas dalam perkerasan yang dirancang dapat memulihkan diri sendiri (Tajudin & Suparma, 2017;Cao, et al, 2018;Li, et al, 2019;González, Norambuena-Contreras, Storey, & Schlangen, 2018).…”
Section: Penggunaan Limbah Pada Perkerasanunclassified